Um olhar semiótico sobre a infância em O olho de vidro do meu avô e outras obras de Bartolomeu Campos de Queirós: o discurso autobiográfico em questão - Moreira, Maria Efigênia Alves (2018)
The present masters dissertation sets out to analyze the representations of childhood in the Brazilian literature, with emphasis on the semiotic analysis of the book O olho de vidro do meu avô and other literary works written by the Brazilian author Bartolomeu Campos d eQueirós. Initially, a survey about the author's critical fortune has been carried out, followed bya brief discussion of the child-juvenile literature as a discourse, which will present clippings of literary books written by different writers, directed or not directed at the child, in which they are approached discursively. Subsequently the semiotic analysis is carried out and, at theend of the work, an interdiscursive relation will be made with other texts of the author, in which he exercises the metalanguage on his fictional proposal, the autobiographical discourse, through the memory of the event and memory-event.Considering the works that will be analyzed semiotically: O olho de vidro do meu avô,Por parte de pai e Ler, escrever e fazer conta de cabeça, this work seeks to understand: the discursive place that the child has occupied; how these narrative enunciations are structured strategically with regard to the language used to cast a glance from the point of view of the child presupposed by the play of enunciation. The identification of this place of enunciation is considered by the enunciator in their specificities through discursive strategies that lead to the simulacrum of the truth. In this sense, this research strengthens the perception of childhood as a construction of meanings, presupposed by discourse. As far as the analysis is concerned, the greimasian semiotics has been used, which allows us to perceive the construction of meanings through the text, the actantial game manifested in the relation between characters and the objects of value placed on the scene, as well as the discursive strategies that allows us to perceive the thematicfigurative isotopies and the enunciation dynamics. As for the categories of analysis, the research will use those consecrated by greimasian semiotics, summarized in the generative path of meaning through the levels of the fundamental narrative and discursive structures, as well as the memory of the event and memory-event. The theoretical contribution is based mainly on the assumptions of the semiotic of Greimas (2016) and on the studies of Fiorin (1993, 2016), Denis Bertrand (2003), Diana Luz Pessoa de Barros (2005) and Mariana Luz Pessoa de Barros (2006, 2016), who present and discuss literary semiotics.